2002
DOI: 10.1046/j.1537-2995.2002.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

The composition of leukapheresis products impacts on the hematopoietic recovery after autologous transplantation independently of the mobilization regimen

Abstract: BACKGROUND : Effects of mobilization regimen on the composition of leukapheresis products (LPs) and on hematopoietic reconstitution after autologous peripheral blood progenitor cell transplantation (PBPCT) are not well known. STUDY DESIGN AND METHODS : The effects of three different mobilization regimens—stem cell factor (SCF) plus granulocyte colony stimulating factor (G–CSF) plus cyclophosphamide (CCP), G–CSF alone, and G–CSF plus CCP—on the composition of LPs from patients with nonhematologic PBPC malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…The parameters were considered either as continuous or as categorical variables and only those reaching a P value o0.1 in the respective univariate analysis were included. 24,25 All P values were considered significant when o0.05. These analyses were performed using the SPSS 15.0 statistical software package (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters were considered either as continuous or as categorical variables and only those reaching a P value o0.1 in the respective univariate analysis were included. 24,25 All P values were considered significant when o0.05. These analyses were performed using the SPSS 15.0 statistical software package (SPSS Inc., Chicago, IL, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical comparisons were performed with a paired Student's t test. Statistical significance was defined as a P value <0.05 [4,5,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore addressed whether pDC CD34 þ precursors coexpress NG2. Interestingly, we found that 12.2% of the pDC precursors (CD34 þ /CD45 þ /CD38 þ / CD123 high /HLADR þ ) [65][66][67] readily coexpress NG2 (Figure 2c). This suggests that, regardless of the status of the MLL locus, the NG2 antigen may be expressed in pDC leukemias if the leukomogenesis process is initially triggered in a pDC CD34 þ precursor readily expressing NG2, which might act as a leukemic-initiating cell.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 95%